TESTING OF SOIL IMPROVEMENT BELOW A HALL FLOOR - Monika Súlovská; Peter Turček; Zuzana Štefunková (Acta Polytechnica CTU Proceedings, 2017)
Construction of a hall situated in North-West Slovakia was prepared in winter. After finishing an elementary ground adaptation in February there were extreme weather conditions: the precipitation exceeded by over 300 % the normal long term measured amount. This indisposition of climate led to a stopping of the construction work. Checks on the required quality of the base course using static load tests showed a failure in performance of compaction. The sampling and laboratory testing of the original and the improved soils are discussed in the paper.